Pengaruh Store Atmosphere Dan Service Quality Terhadap Keputusan Pembelian Pada Cafe Ballad Beach Aie Manih Padang - Agung Septnavirza; Yenni Del Rosa (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the influence of store atmosphere and service quality on purchasing decisions at Cafe Ballad Beach Aie Manih Padang. This study used a quantitative method with data collection through a questionnaire. The study population was unknown and had 118 respondents with a sampling technique using the Cochran formula. Based on the results of the study and data analysis using SPSS (Statistical Product and Service Solutions) shows that: (1) store atmosphere has a positive and significant effect on purchasing decisions, (2) service quality has a positive and significant effect on purchasing decisions, (3) store atmosphere and service quality have a positive and significant effect on purchasing decisions.